An integrating platform for environmental monitoring in museums based on wireless sensor networks - Rodríguez Peralta, Laura M. (2022)
Monitoring the museum’s environment for preventive conservation of art purposes is one major concern to all museums. In order to properly conserve the artwork it is critical to continuously measure some parameters, such as temperature, relative humidity, light and, also, pollutants, either in storage or exhibition rooms. The deployment of a Wireless Sensor Network in a museum can help implementing these measurements in real-time, continuously, and in a much easier and cheap way. In this paper, we present the first testbed deployed in an Contemporary Art Museum, located in Madeira Island, Portugal, and the preliminary results of these experiments. On the other hand, we propose a new wireless sensor node that offers some advantages when compared with several commercially available solutions. Furthermore, we present a system that automatically controls the dehumidifying devices, maintaining the humidity at more constant levels.